A LOOK AT UZBEKISTAN’S DEFENCE REFORMS AND THE SYSTEM OF PROFESSIONAL MILITARY EDUCATION (TAMADDUN NURI JURNALI, 2025)
This article highlights the creative abilities of university students in the field of pedagogy, the level of creative giftedness, characterizing the individual's readiness to create fundamentally new ideas, far from traditional or habitual patterns of thinking, as well as aimed at developing creative abilities, perceived as an independent factor of giftedness, overcoming problems.